Functional Nonequivalency of Actin Isovariants in Arabidopsis - Kandasamy, Muthugapatti K. (American Society for Cell Biology, 2002)
Plants encode at least two ancient and divergent classes of actin, reproductive and vegetative, and each class produces several subclasses of actin isovariants. To gain insight into the functional significance of the actin isovariants, we generated transgenic Arabidopsis lines that expressed a reproductive actin, ACT1, under the control of the regulatory sequences of a vegetative actin gene, ACT2. In the wild-type plants, ACT1 is predominantly expressed in the mature pollen, growing pollen tubes, and ovules, whereas ACT2 is constitutively and strongly expressed in all vegetative tissues and organs, but not in pollen. Misexpression of ACT1 in vegetative tissues causes dwarfing of plants and altered morphology of most organs, and the effects are in direct proportion to protein expression levels. Similar overexpression of ACT2 has little effect. Immunolocalization of actin in leaf cells from transgenic plants with highest levels of ACT1 protein revealed massive polymerization, bundling, and reorganization of actin filaments. This phenomenon suggests that misexpression of ACT1 isovariant in vegetative tissues affects the dynamics of actin and actin-associated proteins, in turn disrupting the organization of actin cytoskeleton and normal development of plants.